Electrodeposited manganese oxide on tailored 3D bimetallic nanofoams for energy storage applications - Siwek, Katarzyna (2019)
Three-dimensional (3D) electrode design has great advantages over its two-dimensional (2D) counterparts, including higher mass loading of active material, enhanced ion diffusion, and electron charge transfer. Commercial 3D porous structures (i.e., Ni foams) do not fit the purpose of the ideal 3D electrode for supercapacitors, in which surface area (per cm(2)) is more important than large pore volume. These characteristics, however, can be tuned by the dynamic hydrogen bubble template (DHBT) electrodeposition, a route that is used to tailor 3D nanostructured (multi-) metallic porous surfaces. In addition to the higher surface area and tailored porosity, these 3D nanostructures can be subsequently functionalized with different species such as metal oxides or other compounds. Therefore, a facile two-step electrochemical fabrication of 3D composite electrode composed of a bimetallic foam functionalized with manganese (Mn) oxide is proposed. The effect of applied current densities on the distribution and structure of Mn oxide (MnOx) electrodeposited over the bare foam is discussed. The results demonstrate that this route paves the way to design high-surface-area architectures for charge storage electrodes with enhanced electrochemical performance (194Fg(-1) mg(-1) of electrodeposited MnOx at 0.5Ag(-1)) and high charge-discharge rate capabilities (91% capacitance retention at 20Ag(-1)) for supercapacitor applications.